Numerical analysis of coupled fluid-structure interaction in magnetohydrodynamic flow and phase change process of nano-encapsulated phase change material systems with deformable heated surface - Ahmed M. Hassan; Mohammed Azeez Alomari; Abdalrahman Alajmi; Abdellatif M. Sadeq; Faris Alqurashi; Mujtaba A. Flayyih; Oguzhan Kazaz (Case Studies in Thermal Engineering)
This study investigates the fluid-structure interaction and heat transfer characteristics of nano-encapsulated phase change material (NEPCM) in a magnetohydrodynamic (MHD) free convection system with a flexible wall. A finite element method coupled with the Arbitrary Lagrangian-Eulerian (ALE) approach was employed to solve the governing equations. The effects of key parameters were examined, including Rayleigh number (Ra = 103-105), Stefan number (Ste = 0.1–0.9), fusion temperature (θf = 0.1–0.9), NEPCM volume concentration (ϕ = 0.01–0.04), oscillation amplitude (A = 0.05–0.15), Hartmann number (Ha = 5–30), and magnetic field inclination angle (γ = 0°–90°). Results show that increasing Ra from 103 to 105 enhanced heat transfer by 256 %, while augmenting Ha from 5 to 30 diminished it by 36.4 %. NEPCM concentration significantly improved heat transfer, with ϕ = 0.04 yielding 31.5 % higher efficiency than ϕ = 0.01. An optimal fusion temperature of θf = 0.5 was identified, providing 6 % better performance than extreme values. The magnetic field angle of 45° offered marginally better heat transfer. These findings provide valuable insights for optimizing thermal management in MHD systems with PCMs and flexible boundaries.